Punch Biopsy Results in Misdiagnosis of Pilomatrixoma - Metin Temel; Ebru Çelik; Mehmet Yaldız; Ali Özgür Karakaş (Turkish Journal of Plastic Surgery, 2017)
Punch biopsy results in misdiagnosis of clinically unsuspected giant pilomatrixoma located over the parotid gland. This study presents a case of pilomatrixoma that was misdiagnosed as a malignant epithelial tumor using punch biopsy. A 25-year-old male was admitted to our clinic for the evaluation of a mass measuring 7×8×8 cm located over the parotid gland. The patient had previously undergone punch biopsy at another clinic because of a lesion in the parotid gland. Punch biopsy revealed a malignant epithelial tumor. The patient underwent excisional biopsy at our clinic. After the biopsy, the residual skin defect was treated using full-thickness skin grafts. The facial nerve and parotid gland were preserved during the biopsy. Histopathological examination of the excisional biopsy material revealed pilomatrixoma. Punch biopsy may result in misdiagnosis of skin lesions in the parotid gland. A differential diagnosis for benign tumors such as pilomatrixoma is essential prior to an aggressive surgical intervention of the parotid gland.